Survey and simulation of space debris using EISCAT UHF - Røynestad, Elisabeth Kristina (UiT Norges arktiske universitet, 2018)
This thesis starts with a review of the evolution of space debris, what is consists of, how it is made, how it is detected and tracked, and why it is such an important topic. Some of the worst collisions have contributed to causing 49% of the total space debris. If the launch rate continues, the "Kessler Syndrome" might become a reality destroying our future outlook for space communication and exploration. Furthermore, a deeper look at the contents is done and what is the impact of these hypervelocity objects. Highly-advanced ground surveillance systems are used to track and catalog the space debris stationed around the globe, and highly sophisticated space debris models are used to estimate the density of the total space debris population in all sizes, shapes and compositions. After 60 years in space, a lot of space debris has accumulated, resulting in a large increase of density in the polar regions. However, objects below 10 cm are not easily detected, but EISCAT UHF is capable detecting the sizes below 10 cm and down to 1 cm by using beampark experiments, its location makes it suitable for detecting polar region debris. The data is then used to confirm the catalog and the models. A 24-hour beampark experiment was done on 4th of January 2018 simultaneously at Tromsø and Svalbard, specifically for this thesis. It statistically measured the range, the Doppler velocity, and the echo strength of space debris. An inversion of apogee and inclination was then done by using these parameters. A modelling of a beampark experiment was simulated, propagating objects through the EISCAT UHF beam. It extracted the data from the ESA MASTER model and the output was the number of detections per day. A comparison of the beampark experiment 2018 campaign with the simulation model indicated that the simplified model shows good correlation with the observations.